Genetic markers of sports performance, interpretation of individual genotypes in the athlete`s genetic passport - Altynova, N. K.; Tokmurzina, S. S.; Kassymbekova, A. M.; Kereyev, T. N.; Musralina, L. Z.; Lebedeva, L. P.; Djansugurova, L. B. (International Journal of Biology and Chemistry, 2024)
Identifying and studying genetic polymorphisms that determine the phenotypes of elite athletes is a highly relevant and significant task in sports science. This research forms the foundational basis for developing what are known as sports genetic passports, which have the potential to revolutionize athlete training and performance through personalized genetic insights. The aim of this review was to analyze genetic markers associated with the development of key athletic qualities - specifically strength, power, speed, and endurance - by conducting a selective systematic review of the existing literature. Through this comprehensive review, we were able to select single nucleotide polymorphisms (SNPs) that are associated with specific athletic traits by examining the functions of their corresponding gene products. This approach offers a valuable framework for interpreting sports genetic markers within genetic passports. These genetic markers can provide scientists and practitioners in the fields of physical culture and sports medicine with the latest and most compelling evidence in exercise genomics, thereby facilitating more personalized and effective training strategies. As a result, we have compiled a set of 40 widely recognized genetic markers linked to athletic performance-strength, speed, and endurance. This compilation serves as a crucial resource for further research and practical applications aimed at optimizing athletic potential and enhancing performance.